Adaptation in focus: Kenya’s efforts in climate reporting and resilience - Njuguna, Lucy; Cramer, Laura K.; Jalang'o, Dorcas; Wendo, Hausner (2025)
Kenya is taking significant strides in climate reporting and resilience-building by successfully submitting its first Biennial Transparency Report (BTR) under the Paris Agreement. Developed in collaboration with key stakeholders, the report outlines the country’s progress in reducing greenhouse gas emissions, adapting to climate change, and identifying areas where additional support is needed. It also highlights Kenya’s proactive efforts to address climate challenges, particularly in the face of natural disasters that annually cost the country 3–5% of its GDP. This milestone showcases Kenya’s commitment to global climate action and emphasizes the need for robust adaptation strategies to secure a sustainable future.